As crianças apresentam sinais e sintomas que compõem um quadro pós-COVID-19? - Giovanna Guilherme Barcelos; Renata Machado Pinto; Paula de Oliveira Caetano Queiroz; Adriel Felipe de Rezende; Jordanna Ferreira Lousek; Mariana Braga Teixeira (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVES: To carry out a systematic review of the clinical manifestations of long-term COVID in children. METHODS: The starting point was: "What are the clinical manifestations in children with long-term COVID syndrome?". A systematic literature review was conducted in SCOPUS, Embase, NCBI, and MedRxiv databases. Articles on the clinical picture of long-term COVID in the pediatric population were included, with the cohort, case-control, cross-sectional studies, and case reports published in 2020 and 2021. The selection and analysis were performed by four researchers independently, following the Preferred Reporting Items for Systematic Reviewers and Meta-analysis guidelines. RESULTS: Reviewers identified 6,279 potential articles, of which 8 met the inclusion criteria. The sampling in the selected publications ranged from 1 to 2,500 participants, whose age range ranged from 3 months to 18 years. The most reported symptoms in long-term COVID were: fatigue, upper and lower respiratory tract symptoms, sleep disturbances, and neurological symptoms. The duration of these symptoms ranged from four weeks to eight months. Some articles also reported pediatric inflammatory multisystem syndrome (SIM-P) in the long-term COVID. CONCLUSION: Long-term COVID affects on average 15.5% of children after infection, lasting from 4 to 32 weeks. The main symptoms were fatigue and dyspnea, followed by musculoskeletal, respiratory, neurological, and sleep disorders. Furthermore, it was impossible to elucidate these cases risk factors and outcomes in this study.